2022
DOI: 10.1080/21645515.2022.2144048
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers’ attitudes on mandates, incentives, and strategies to improve COVID-19 vaccine uptake: A mixed methods study

Abstract: Healthcare workers are a trusted health information source and are uniquely positioned to reduce the burden of the COVID-19 pandemic. The purpose of this sequential exploratory mixed methods study was to understand attitudes of healthcare workers working in Massachusetts during the COVID-19 pandemic regarding strategies to improve COVID-19 vaccine utilization, including vaccine mandates and incentives. Fifty-two individuals completed one-on-one interviews between April 22 nd and Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…The last three studies from Europe (UK, Poland, and the Czech Republic) showed conflicting results regarding HCWs' acceptance of vaccine mandates for HCWs (acceptance rates: 6-75%) [37,40,57]. A generally supportive attitude was reported in a series of seven studies from the US, while data from two Australian studies revealed that Australian HCWs were divided about accepting COVID-19 vaccine mandates for HCWs [44][45][46][58][59][60][61][62][63]. In three studies (one from India, one from Mongolia, and one from Pakistan), most participants were in favor of vaccine mandates for COVID-19, while in another study from India, 60% of participants were against them [64][65][66][67].…”
Section: Main Findingsmentioning
confidence: 99%
“…The last three studies from Europe (UK, Poland, and the Czech Republic) showed conflicting results regarding HCWs' acceptance of vaccine mandates for HCWs (acceptance rates: 6-75%) [37,40,57]. A generally supportive attitude was reported in a series of seven studies from the US, while data from two Australian studies revealed that Australian HCWs were divided about accepting COVID-19 vaccine mandates for HCWs [44][45][46][58][59][60][61][62][63]. In three studies (one from India, one from Mongolia, and one from Pakistan), most participants were in favor of vaccine mandates for COVID-19, while in another study from India, 60% of participants were against them [64][65][66][67].…”
Section: Main Findingsmentioning
confidence: 99%